2020
DOI: 10.4103/jips.jips_70_20
|View full text |Cite
|
Sign up to set email alerts
|

A finite element analysis to study the stress distribution on distal implants in an all-on-four situation in atrophic maxilla as affected by the tilt of the implants and varying cantilever lengths

Abstract: Aim: The aim of this work was to evaluate stress distribution on implants in All-on-Four situation with varying distal implant angulations (30°,40°,45°) and varying cantilever lengths (4 mm, 8 mm, 12 mm, 16 mm) in atrophic maxilla using finite element analysis. Setting and Design: A in vitro study, finite element analysis. Materials and Methodology: Three-dimensional finite element model of an edentulous maxilla res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…It showed that tilted implants produced higher peri-implant bone stress compared with the vertical implants, and the stresses were increased when the inclination of the implant was increased. These results were consistent with previous finite element analyses that examine the load transmission using different implant inclinations [ 22 , 23 ]. In addition, because of the distally tilted implants are splined with other three implants in a rigid metal framework, the rigidity of the framework and the anterior and posterior spread of the implants can reduce the stresses transmitted to the tilted implants [ 24 , 25 ], so the stresses at the neck of the tilted implant of the All-on-4 implant photoelastic models are lower compared with the single implants of the same inclination.…”
Section: Discussionsupporting
confidence: 92%
“…It showed that tilted implants produced higher peri-implant bone stress compared with the vertical implants, and the stresses were increased when the inclination of the implant was increased. These results were consistent with previous finite element analyses that examine the load transmission using different implant inclinations [ 22 , 23 ]. In addition, because of the distally tilted implants are splined with other three implants in a rigid metal framework, the rigidity of the framework and the anterior and posterior spread of the implants can reduce the stresses transmitted to the tilted implants [ 24 , 25 ], so the stresses at the neck of the tilted implant of the All-on-4 implant photoelastic models are lower compared with the single implants of the same inclination.…”
Section: Discussionsupporting
confidence: 92%
“…[ 21 ] in All-on-Four study suggested that the stress was maximum at the distal bone–implant interface due to the close proximity of load application. Lima et al .,[ 28 ] Saleh Saber et al .,[ 29 ] Sanino et al .,[ 16 ] Kumari et al .,[ 30 ] Horita et al .,[ 10 ] Deste and Durkan,[ 31 ] and Oh et al . [ 32 ] suggested that the maximum stress that occurred in the implant is also due to the fact that a vertical load is acting on an inclined implant.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the more rigid over denture material transfers the load direct to bar then implants and bone via high bending effect that increase stresses and deformations on implant complex and cortical bone. This is augmented by Kumari et al in 2020 as they assessed different cantilever lengths and found that with increasing the cantilever length more stresses are exerted over the terminal implant [29] . Bar presence resulted in over constrained implants that increase its stresses levels under loading in comparison to separate supporting implants [30,31] .…”
Section: Discussionmentioning
confidence: 99%